2002
DOI: 10.1046/j.1365-2230.2002.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR and DQ polymorphisms in bullous pemphigoid from northern China

Abstract: Bullous pemphigoid (BP) is an autoimmune disease mediated by autoantibodies against hemidesmosome components. This study used PCR-sequence-specific primers to genotype polymorphisms in HLA-DR and DQ in 25 BP patients and 57 normal controls from northern China. We found lower frequencies of DRB1*08 (DR8) and DRB1*08/DQB1*06 (DR8/DQ6) haplotypes in BP patients than in controls (4.08% vs. 15.19% and 1.54% vs. 13.82%, respectively; P < 0.05), suggesting a protective role for DR8 and DR8/DQ6 haplotypes in BP patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
0
16
0
2
Order By: Relevance
“…Previous reports showed that DQB1*0301 occurs more frequently in Caucasian patients with BP and that HLA-DRB1*04, DRB1*1101, and DQB1*0302 occur more frequently in Japanese patients with BP compared with healthy controls, indicating that HLA differences influence susceptibility to BP (Zakka et al, 2011). The association between HLA class II genes and BP in the Chinese population has not been clearly shown, with only two protective alleles previously reported (Gao et al, 2002). In our study, CD4 þ T-cell response was restricted to HLA-DR in patients with BP.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports showed that DQB1*0301 occurs more frequently in Caucasian patients with BP and that HLA-DRB1*04, DRB1*1101, and DQB1*0302 occur more frequently in Japanese patients with BP compared with healthy controls, indicating that HLA differences influence susceptibility to BP (Zakka et al, 2011). The association between HLA class II genes and BP in the Chinese population has not been clearly shown, with only two protective alleles previously reported (Gao et al, 2002). In our study, CD4 þ T-cell response was restricted to HLA-DR in patients with BP.…”
Section: Discussionmentioning
confidence: 96%
“…Several cases of DPP4‐i‐associated BP have been reported as non‐NC16A‐BP . The genetic associations are studied in autoimmune diseases, including BP . In addition, some adverse drug reactions are strongly related to genetic background .…”
Section: Discussionmentioning
confidence: 99%
“…Th1 responses to NC16a were seen in another study in healthy controls carrying the human leucocyte antigen (HLA) class 2 allele DQβ1*0301 , which is known to be associated with BP in North American Caucasians, approximately 35% of whom have this haplotype compared to 16% of controls . However, this is not essential to the BP disease phenotype in other ethnic groups . Recent computer modelling suggests affinity for this HLA binding in 13 peptide sequences in BP180.…”
Section: Discussionmentioning
confidence: 99%